2020
DOI: 10.3389/fimmu.2020.00265
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Engineering of the Kidney to Permanently Silence MHC Transcripts During ex vivo Organ Perfusion

Abstract: Organ gene therapy represents a promising tool to correct diseases or improve graft survival after transplantation. Polymorphic variation of the major histocompatibility complex (MHC) antigens remains a major obstacle to long-term graft survival after transplantation. Previously, we demonstrated that MHC-silenced cells are protected against allogeneic immune responses. We also showed the feasibility to silence MHC in the lung. Here, we aimed at the genetic engineering of the kidney toward permanent silencing o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 53 publications
1
36
0
Order By: Relevance
“…Researchers have access to several molecular tools to disrupt β2M expression, and the choice depends on the outcome needed. Post-transcriptional manipulation by RNA interference (RNAi), either using small interfering RNA (siRNA) or short hairpin RNA (shRNA), stably downregulated or silenced the expression of HLA proteins in B-lymphocyte cell lines ( 58 ) in conjunction with human ESCs ( 59 ), iPSCs ( 60 ), primary human hepatocytes ( 61 ), endothelial cells ( 62 , 63 ) and in a perfusion system at the whole organ level in rat kidney ( 64 ). Silencing with RNAi proved to be stable even after the iPSCs were differentiated to megakaryocytes and even platelets ( 60 ).…”
Section: Hla Depletionmentioning
confidence: 99%
“…Researchers have access to several molecular tools to disrupt β2M expression, and the choice depends on the outcome needed. Post-transcriptional manipulation by RNA interference (RNAi), either using small interfering RNA (siRNA) or short hairpin RNA (shRNA), stably downregulated or silenced the expression of HLA proteins in B-lymphocyte cell lines ( 58 ) in conjunction with human ESCs ( 59 ), iPSCs ( 60 ), primary human hepatocytes ( 61 ), endothelial cells ( 62 , 63 ) and in a perfusion system at the whole organ level in rat kidney ( 64 ). Silencing with RNAi proved to be stable even after the iPSCs were differentiated to megakaryocytes and even platelets ( 60 ).…”
Section: Hla Depletionmentioning
confidence: 99%
“…Consequently, it has been suggested that direct targeting of the graft vasculature may reduce alloimmunity and prolong graft survival 10 . Previous efforts to modify the extent of endothelial activation were made in the form of immunocloaking the vasculature using a temporary barrier 11 and silencing MHC antigen expression 12 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Experimental evidence for the delivery of MSCs [13–15], gene therapies [28], nanoparticles [30,31] and other IRI targeted [33–39] therapies during NMP is increasing and the results have been positive. However, none of the approaches have been tested in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…delivered lentiviral vectors directly to the organ. This delivered encoding shRNA targeting beta2 microglobulin and the class II transactivator, in addition to a sequence for a secreted nanoluciferase [28]. After kidney transplantation and 6 weeks follow up, bioluminescence was detected in the plasma and urine of recipients of engineered kidneys, indicating stable gene expression.…”
Section: Gene Therapiesmentioning
confidence: 99%
See 1 more Smart Citation